Mechanisms, Assessment, and Management of Drug-Induced Pigmentation in Clinical Pharmacology - Alnughaymishi, Luay; AlSahabi, Fayez Homod; Othman, Rawan Abdo; Alsuwat , Sabah Hamoud O; Alzoman, Moneerah Mohammed Humood; Alghamdi, Faisal Abdullah; Alfehaid, Fahad Sami Abdulaziz; Alshammari, Abdulaziz Salem Shafi; Alnami, Hussam Ahmed Alhassan; Alrashoud, Saad Saud Saad; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Drug-induced pigmentation (DIP) is a clinically significant adverse effect resulting from diverse pharmacologic agents. It manifests through mechanisms such as melanogenesis stimulation, drug/metabolite deposition, and postinflammatory changes, often leading to cosmetic and psychosocial concerns. Aim: To review the mechanisms, clinical assessment, and management strategies for DIP, emphasizing preventive and therapeutic approaches. Methods: A comprehensive literature review was conducted, analyzing pharmacologic classes implicated in DIP, pathophysiologic mechanisms, histopathologic features, and treatment modalities. Clinical evaluation protocols and interprofessional management strategies were synthesized from current evidence. Results: Over 50 drug classes, including antimicrobials, antimalarials, psychotropics, chemotherapeutics, and heavy metals, are associated with DIP. Mechanisms include enhanced melanogenesis, dermal deposition of lipophilic drugs, and inflammatory sequelae. Histopathology reveals nonspecific but diagnostic patterns, such as melanin-laden macrophages or drug granules. Management involves drug substitution or dose reduction, photoprotection, topical depigmenting agents, and procedural interventions like laser therapy. Prognosis is generally favorable, though pigmentation may persist, especially with dermal deposition or extracutaneous involvement. Conclusion: Early recognition and individualized management of DIP are essential to prevent progression and optimize patient outcomes. Preventive strategies, patient education, and multidisciplinary collaboration remain critical components of care.